Dynamic energy absorption behavior of lattice material filled with shear thickening fluid. (2017) - Wu, Xianqian; Yin, Qiuyun; Huang, Chenguang; Zhong, Fachun
Abstract: In the present research the dynamic energy absorption behavior of lattice material filled with shear thickening fluid (STF) is studied by the modified split Hopkinson pressure bar (SHPB) apparatus. The nominal engineering stresses versus strain curves are measured to analyze the dynamic energy absorption behavior of the combined material. The dynamic behavior of lattice material is also measured as a comparison. The results show the dynamic strength of the lattice material is about 3 MPa, which is a little higher than the static strength of about 2.3 MPa because of the inertial effect during impact. However, when filled with STF, the combined material shows extraordinary energy absorption behavior when compared to the empty lattice material. The stress of the lattice material filled with STF increase almost linearly to about 9 MPa and then increases slowly with the increase of strain. The excellent energy absorption behavior of the lattice material filled with STF could be explained by the interaction between the lattice cores and the STF during compression. For the lattice material, while some of cores buckling, it will lose the load capacity. While filled with STF, if the initial buckling of some of the lattice cores happens during impact, the strong lateral drag force is generated by the ambient STF due to the fast lateral velocities of the cores, leading to the great increase of its dynamic energy absorption behavior.